The Effectiveness Of The Implementation Of Sporadic Land Registration At The Boyolali District Land Office (Indonesian Journal of Agrarian Law, 2026)
This study examines the effectiveness of sporadic land registration services at the Boyolali District Land Office, Central Java, Indonesia. Sporadic land registration serves as the primary mechanism for communities to obtain land certificates as legal evidence of land ownership; however, its implementation has not yet achieved optimal effectiveness. The objective of this study is to analyse the implementation of sporadic land registration and identify the factors influencing its effectiveness. This research employs an empirical legal approach by combining normative analysis of land regulations with field research through interviews with Land Office officials and direct observation of the registration process. The findings reveal that the implementation procedures generally comply with the Basic Agrarian Law and Government Regulation No. 24 of 1997. Nevertheless, the completion rate of land registration applications remains below the expected target, while the average processing time exceeds the established standard of ninety-eight working days. Using Soerjono Soekanto’s theory of legal effectiveness, this study identifies several major obstacles, including the limitations of the negative publication system with positive elements, the shortage of surveyors, inadequate digital infrastructure, and low public awareness regarding land registration. The study contributes to the development of empirical legal studies by demonstrating how administrative, technological, and social factors simultaneously affect land registration effectiveness. It concludes that sporadic land registration in Boyolali Regency has not yet operated effectively and requires institutional and technological improvements. Therefore, this study recommends increasing the number of surveyors, simplifying administrative procedures, accelerating electronic land services, and strengthening public legal awareness programmes.